Investigation of the Effects of Roller Burnishing on the Surface Quality of Inconel 718 Alloy - Celik, Mahmut (Fırat University, 2023)
The roller burnishing method is a low-cost and effective surface improvement method that has been frequently preferred in recent years. In the method, a rolling element is pressed against the workpiece surface with a certain force, and the irregularities on the surface are removed by cold deformation. Thus, surface roughness is removed and surface quality is increased. In this study, samples manufactured from Inconel 718 alloy by turning method were subjected to burnishing process. In the process, the compression force, feed rate and number of passes parameters were changed at 4 different levels and the effects of these parameters on the surface quality were investigated experimentally. In the study, in which Taguchi L16 experimental design approach was adopted, it was determined that the surface roughness was improved by an average of 94.29%. On the other hand, as a result of the data obtained from the Signal/Noise ratio analysis, it was determined that the most effective parameter on the surface roughness improvement ratio was the number of passes, followed by the feed rate and compression force parameters, respectively.

Ezerek parlatma yöntemi son yıllarda sıklıkla tercih edilen düşük maliyetli ve etkili bir yüzey iyileştirme yöntemidir. Yöntemde bir yuvarlanma elemanı iş parçası yüzeyine belirli bir kuvvetle bastırılarak yüzey üzerindeki düzensizlikler soğuk deformasyona uğratılarak giderilir. Böylece yüzey pürüzlülükleri giderilerek yüzey kalitesi artırılır. Bu çalışmada Inconel 718 alaşımından tornalama yöntemiyle imal edilmiş numuneler ezerek parlatma işlemine tabi tutulmuşlardır. İşlemde baskı kuvveti, ilerleme miktarı ve paso sayısı parametreleri 4’er farklı seviyede değiştirilmiş ve bu parametrelerin yüzey kalitesi üzerindeki etkileri deneysel olarak inceleniştir. Taguchi L16 deneysel tasarım yaklaşımı benimsenen çalışmada yüzey pürüzlülüklerin ortalama % 94,29 oranında iyileştirildiği tespit edilmiştir. Öte yandan Sinyal/Gürültü oranı analizinden elde edilen veriler neticesinde yüzey pürüzlülüğü iyileşeme oranı (YPİO) üzerinde en etkili parametrenin paso sayısı olduğu ve bunu sırasıyla ilerleme miktarı ve baskı kuvveti parametrelerinin takip ettiği tespit edilmiştir.
Ezerek Parlatma Yönteminin Inconel 718 Alaşımının Yüzey Kalitesi Üzerindeki Etkilerinin Araştırılması
Keywords: Engineering; Mühendislik